The Development of an IMP Metallo-β-lactamase Detection Assay Using a Bioinformatic Approach. (4th October 2017) - Smith, Hayden; Hansen, Nancy
Abstract: Background: Carbapenem antibiotic resistance in Gram-negative bacteria is becoming increasingly common. One such resistance gene, IMP metallo-β-lactamase, has been found worldwide. With 48 different IMP alleles across many genera of bacteria, no known assay can detect all 48 IMP alleles. We developed a PCR-based assay to detect IMP genes using a novel bioinformatic approach to design primers that would recognize all gene variants. Methods: Computer simulation of primers was accomplished by using common PCR primer design heuristics as parameters. Following primer simulation, an all-against-all gene comparison was done to calculate potential primer sets. The minimum number of primer sets required to detect all IMP genes was subsequently found by iterative deduction. The predicted primer sets were tested against 7 IMP-producing bacterial isolates (IMP-1, 4, 7, 8, 14, 18, 27 from Serratia, Enterobacteriaceae, Pseudomonas, and Klebsiella spp .) and one synthesized gene of IMP-35. These isolates were chosen to represent the full genetic spectrum of the IMP family. The remaining 40 genes were evaluated based on gene sequences obtained from GenBank. Results: The in silico analysis showed 6 primer sets were needed to detect all known IMP genes. PCR amplification of template DNA isolated from the 8 strains showed that primer sets 1 and 4 could detect all 8 IMP isolates while the remaining 4 sets (2, 3, 5, 6) had distinct amplification patterns that could be used together to identify a specific IMP gene group. Effectiveness of these primer sets in IMP identification was demonstrated by testing a clinical isolate containing an unidentified carbapenem resistant bacterium. The IMP-27 gene was identified by PCR amplification using the IMP-specific primers designed and confirmed by sequence analysis. Conclusion: A bioinformatic approach can be used to create an assay for bacterial resistance. The assay developed with this approach can detect and classify all known IMP metallo-β-lactamase genes in carbapenem resistant Gram-negative bacteria. Such information could aid in guiding treatment and evaluating the epidemiology of IMP-producing bacteria. Disclosures: All authors: No reported disclosures.